1984
DOI: 10.1093/petrology/25.3.766
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Textures and Metamorphic Evolution of Sapphirine-bearing Granulites from the Gruf Complex, Italian Central Alps

Abstract: Mineral chemistries and textures are described from a suite of sapphirine-bearing granulites from the Gruf Complex of the Italian Central Alps. The granulites contain combinations of garnet, orthopyroxene, sapphirine, sillimanite, cordierite, biotite, quartz, spinel, corundum, staurolite, plagioclase, K-feldspar, ilmenite and rutile, in assemblages with low (usually negative) variance. They are outstanding in that they preserve a textural and chemical record of a protracted metamorphic evolution.Reaction textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 31 publications
10
63
0
Order By: Relevance
“…Most of the previous interpretations considered the Gruf complex as a migmatitic unit that at least locally also suffered granulite-facies metamorphism during Alpine metamorphism (Droop and Bucher-Nurminen 1984;Gebauer 2003, Schmitz et al 2009). Structurally, the Gruf complex was regarded as either the eastern continuation of the Adula nappe (Schmid et al 1996a, b;Davidson et al 1996;Frey and Ferreiro Mählmann 1999;Berger et al 2005) or an equivalent of the Bellinzona-Dascio zone (Wenk 1973;Wenk and Cornelius 1977;Milnes and Pfiffner 1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previous interpretations considered the Gruf complex as a migmatitic unit that at least locally also suffered granulite-facies metamorphism during Alpine metamorphism (Droop and Bucher-Nurminen 1984;Gebauer 2003, Schmitz et al 2009). Structurally, the Gruf complex was regarded as either the eastern continuation of the Adula nappe (Schmid et al 1996a, b;Davidson et al 1996;Frey and Ferreiro Mählmann 1999;Berger et al 2005) or an equivalent of the Bellinzona-Dascio zone (Wenk 1973;Wenk and Cornelius 1977;Milnes and Pfiffner 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Granulites and charnockites formed under ultra-high temperature conditions of T = 920-940°C and P = 8.5-9.5 kbar (Galli et al 2011). Droop and Bucher-Nurminen (1984), and Schmitz et al (2009) suggested an Alpine age for the granulites, whereas Huber (1999), Burri et al (2005) and Galli et al (2011) envisaged a pre-Alpine age. Subsequently, the charnockites have been dated at 282-260 Ma (U-Pb on zircon) placing granulite facies conditions in the Permian (Galli et al 2012).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, later evidence of subtle partial melting was found [62], suggesting that the orthopyroxene-bearing assemblages formed under suprasolidus conditions. Although some studies have recorded mineral assemblages with prograde subsolidus orthopyroxene e.g., [63,64], these situations generally involve infiltration of a low H 2 O activity fluid (aH 2 O), such as CO 2 -rich fluids or highly concentrated brines, and occur in rocks that have experienced granulite facies temperatures. An example of this is the formation of fine-grained orthopyroxene-andalusite symplectites under low aH 2 O conditions during retrogression of pelitic granulites, described by Ballèvre, et al [65].…”
Section: Limitations Of the Modellingmentioning
confidence: 99%
“…Fine-grained symplectitic intergrowths that have been locally developed are generally interpreted to have formed during retrograde breakdown of high-grade phases (Droop & Bucher-Nurminem 1984, Ballèvre et al 1997, Nijland et al 1998 between 890 -1160 ±50°C. We estimate the P-T conditions of the Sil -Spl -Crd -Spr -Qtz assemblage studied here between 900 -950 ±50°C and 9 -10 ±1 kbar.…”
Section: Located the Fmas [Qz]mentioning
confidence: 99%